2015
DOI: 10.1074/jbc.m115.666503
|View full text |Cite
|
Sign up to set email alerts
|

The Disulfide Bond, but Not Zinc or Dimerization, Controls Initiation and Seeded Growth in Amyotrophic Lateral Sclerosis-linked Cu,Zn Superoxide Dismutase (SOD1) Fibrillation

Abstract: Aggregation of copper-zinc superoxide dismutase (SOD1) is a defining feature of familial ALS caused by inherited mutations in the sod1 gene, and misfolded and aggregated forms of wildtype SOD1 are found in both sporadic and familial ALS cases. Mature SOD1 owes its exceptional stability to a number of posttranslational modifications as follows: formation of the intramolecular disulfide bond, binding of copper and zinc, and dimerization. Loss of stability due to the failure to acquire one or more of these modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 66 publications
2
66
0
Order By: Relevance
“…WT hSOD1 is much more resistant to reduction by both systems. Disulfide reduction and metal ion removal may trigger SOD1 aggregation (42), but, in fact, disulfide bonds cause the initiation of its fibrillation (43). In our study, the reduced mutant hSOD1 was detected to be catalytically active.…”
Section: Discussionsupporting
confidence: 45%
“…WT hSOD1 is much more resistant to reduction by both systems. Disulfide reduction and metal ion removal may trigger SOD1 aggregation (42), but, in fact, disulfide bonds cause the initiation of its fibrillation (43). In our study, the reduced mutant hSOD1 was detected to be catalytically active.…”
Section: Discussionsupporting
confidence: 45%
“…It has been reported that certain posttranslational modifications of wild-type SOD1 (SOD1 WT ), including oxidation [6, 12, 16, 26, 27, 37] and demetallation [47] induce its misfolding in vitro , suggesting that even SOD1 WT can acquire toxic properties like those associated with ALS-linked mutants of SOD1. In transgenic mice, ~5–20 fold higher levels of SOD1 WT expression cause SOD1 aggregation and neuronal pathology in the CNS in aged mice [24, 35, 36], whereas expressing low levels of human SOD1 WT does not result in ALS-like disease [9, 14, 28].…”
Section: Introductionmentioning
confidence: 99%
“…In familial and sporadic ALS cases, post-translational modifications induced by environmental factors play a significant role in disease progression (Barber and Shaw, 2010; Chattopadhyay et al, 2015; Pasinelli and Brown, 2006). Specifically, glutathionylation of C111, oxidative modification of W32, and phosphorylation of T2 or S58/T59 have been identified in human SOD1 (Coelho et al, 2014; Wilcox et al, 2009).…”
Section: Introductionmentioning
confidence: 99%